LCLS in—photon out: fluorescence measurement of neon using soft x-rays. (9th January 2018) - Obaid, Razib; Buth, Christian; Dakovski, Georgi L; Beerwerth, Randolf; Holmes, Michael; Aldrich, Jeff; Lin, Ming-Fu; Minitti, Michael; Osipov, Timur; Schlotter, William; Cederbaum, Lorenz S; Fritzsche, Stephan; et al.
Abstract: We measured the fluorescence photon yield of neon upon soft x-ray ionization (∼1200 eV) from the x-ray free-electron laser at Linac Coherent Light Source, and demonstrated the usage of a grazing incidence spectrometer with a variable line spacing grating to perform x-ray fluorescence spectroscopy on a gas phase system. Our measurements also allowed us to estimate the focal size of the beam from the theoretical description developed, in terms of the rate equation approximation accounting for photoionization shake off of neutral neon and double auger decay of single core holes.